Selection for resistance to cassava mosaic disease in African cassava germplasm using single nucleotide polymorphism markers - Codjia, E.D.; Olasanmi, B.; Agre, A.P.; Uwugiaren, R.; Ige, A.D.; Rabbi, I.Y. (Academy of Science of South Africa, 2022)
Cassava mosaic disease (CMD) is one of the main constraints that hamper cassava production. Breeding for varieties that are CMD resistant is a major aim in cassava breeding programmes. However, the use of the conventional approach has its limitations, including a lengthy growth cycle and a low multiplication rate of planting materials. To increase breeding efficiency as well as genetic gain of traits, SNP markers can be used to screen and identify resistant genotypes. The objective of this study was to predict the performance of 145 cassava genotypes from open-pollinated crosses for CMD resistance using molecular markers. Two SNP markers (S12_7926132 and S14_4626854), previously converted into Kompetitive allele-specific PCR (KASP) assays, as well as CMD incidence and severity scores, were used for selection. About 76% of the genotypes were revealed to be resistant to CMD based on phenotypic scores, while over 24% of the total population were found to be susceptible. Significant effects were observed for alleles associated with marker S12_7926132 while the other marker had non-significant effects. The predictive accuracy (true positives and true negatives) of the major CMD2 locus on chromosome 12 was 77% in the population used in this study. Our study provides insight into the potential use of marker-assisted selection for CMD resistance in cassava breeding programmes.